The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.14202/vetworld.2020.2713-2727
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance situation in animal health of Bangladesh

Abstract: Antimicrobial resistance (AMR) is a crucial multifactorial and complex global problem and Bangladesh poses a regional and global threat with a high degree of antibiotic resistance. Although the routine application of antimicrobials in the livestock industry has largely contributed to the health and productivity, it correspondingly plays a significant role in the evolution of different pathogenic bacterial strains having multidrug resistance (MDR) properties. Bangladesh is implementing the National Action Plan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 50 publications
3
39
1
Order By: Relevance
“…Antibiotic therapy is still considered as a tool in the treatment of FC. However, AMR has become a global problem as resistant isolates have emerged by the excessive and unjustified use of antimicrobials [5,19,67]. The P. multocida strains of the present study showed resistance to ampicillin (90.91%), tetracycline (90.91%), and nalidixic acid (63.64%) according to the EUCAST breakpoints (Figure -1).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Antibiotic therapy is still considered as a tool in the treatment of FC. However, AMR has become a global problem as resistant isolates have emerged by the excessive and unjustified use of antimicrobials [5,19,67]. The P. multocida strains of the present study showed resistance to ampicillin (90.91%), tetracycline (90.91%), and nalidixic acid (63.64%) according to the EUCAST breakpoints (Figure -1).…”
Section: Resultsmentioning
confidence: 62%
“…However, all of the tested isolates were sensitive to colistin, suggesting that colistin could effectively be used for the treatment of FC with P. multocida considering the serious worldwide concern on AMR. Frequent and excessive use of antibiotics in the livestock of Bangladesh [19,21] might have a role in AMR development against multiple antibiotics in clinical infections like FC [75,76].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial chicken and fish farms perform intensive operations to increase production and minimize disease prevalence. Many types of drugs, including antimicrobials, vitamins, minerals, and antimicrobial growth promoters are extensively used in commercial chicken and aquaculture production sectors [ 16 , 17 , 18 , 19 , 20 , 21 ]. Despite the massive benefit of treating animal diseases using antimicrobial drugs, the resulting emergence of antibiotic resistance has raised global concerns [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many farmers in Bangladesh are less aware of the negative impact of excessive, irrational, and prophylaxis use of antibiotics in animals, and aquaculture. Inadequate veterinary healthcare facilities, insufficient monitoring and regulatory services on antibiotic usage, high occurrence of diseases, and malpractices by unqualified veterinary healthcare providers (quack, drug sellers, and animal feed dealers) contributed a crucial role in the increased and misusage of antibiotics in animal health sectors [ 21 ].…”
Section: Introductionmentioning
confidence: 99%